Management of an unexpected laparoscopic complication in a low-resource setting - Hasabe, Rakesh; Tripathi, Neha S.; Bapat, Supriya (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Objective of this study is to describe the management of a rare and unexpected complication due to the breakage of a surgical blade tip during vaginal coring in a case of total laparoscopic hysterectomy in a low-resource setting. In this case report we are describing an unexpected complication which arose when a No. 11 surgical blade tip broke and got displaced during vaginal coring in a case of total laparoscopic hysterectomy with bilateral salpingectomy. When it was not possible to locate the blade tip in the abdominopelvic cavity, its location was triangulated using thorough manual examination followed by live imaging, and the blade tip was retrieved without damage to surrounding structures. The details of the loss and retrieval of the blade tip emphasize the need for a systematic approach to instrument upkeep, personnel training, and judicious use of available imaging in low-resource settings to manage unexpected and rare complications quickly and effectively during laparoscopic surgeries.